A contribution to the knowledge of leaf-mining Phyllocnistis Zeller, 1848 associated with Baccharis (Asteraceae), with description of two new species from Peru (Lepidoptera: Gracillariidae) - Cerdeña, José; Farfán, Jackie; Vargas, Héctor A.; Huanca-Mamani, Wilson; Gonçalves, Gislene L.; Moreira, Gilson R. P. (Zootaxa, 2022)
We provide new information on Neotropical Phyllocnistis Zeller (Gracillariidae) associated with Baccharis (Asteraceae) in the Andes region. Two new species are described, P. canta Cerdeña & Farfán, n. sp. and P. elongata Cerdeña & Farfán, n. sp., from the western slopes of the Andes of Peru between 2,000 and 3,000 m elevation, both associated with Baccharis latifolia (R.&P.) Pers. The type locality of P. baccharidis Hering is confirmed; immature stages were found at 1,300 m feeding on Baccharis tucumanensis Hook. & Arn. in Quebrada las Higueras (Tucumán, Argentina). Four new locality records for P. furcata Vargas & Cerdeña are provided, extending its distribution by 450 km to the north of the type locality.